The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1677/joe.0.1080069
|View full text |Cite
|
Sign up to set email alerts
|

Na-K-ATPase-inhibiting and glucose-6-phosphate dehydrogenase-stimulating activity of plasma and hypothalamus of the Okamoto spontaneously hypertensive rat

Abstract: The plasma of normal man and the rat, and an acetone extract of hypothalamus from the rat, have an ability to inhibit Na-K-ATPase which is related directly to salt intake. The ability of the plasma to inhibit Na-K-ATPase is raised in essential hypertension. The ability of plasma and of an acetone extract of hypothalamus from six spontaneously hypertensive (SHR) rats and six normotensive control (WKY) rats to inhibit Na-K-ATPase of fresh guinea-pig kidney was studied using cytochemical bioassay techniques. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…It is difficult to reconcile these ambiguous results concerning the Na + ,K + -ATPase inhibition with those of Millet et al, 21 who reported that, compared with that of WKY, plasma from SHR exerts a very marked stimulation of the activity of the renal glucose 6-phosphate dehydrogenase in fresh guinea pig kidney proximal tubule; this stimulation was usually associated with reciprocal changes in Na + ,K + -ATPase activity. They have also confirmed that SHR plasma does induce a transient inhibition of Na + ,K + -ATPase activity in the same cells.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is difficult to reconcile these ambiguous results concerning the Na + ,K + -ATPase inhibition with those of Millet et al, 21 who reported that, compared with that of WKY, plasma from SHR exerts a very marked stimulation of the activity of the renal glucose 6-phosphate dehydrogenase in fresh guinea pig kidney proximal tubule; this stimulation was usually associated with reciprocal changes in Na + ,K + -ATPase activity. They have also confirmed that SHR plasma does induce a transient inhibition of Na + ,K + -ATPase activity in the same cells.…”
Section: Discussionmentioning
confidence: 84%
“…The difference between these and our results cannot be explained by different Na + intakes, as with the diets of both their and our animals the urinary Na + excretion averaged 1 mmol/24 hr. Methodological differences are more likely to be involved, including the origin of the Na + ,K + -ATPase (rat or guinea pig semipurified enzyme or tissue slices), the amount of plasma studied (1.8 or down to 10~5), the time course of inhibition (stable or transient), and our use of deproteinized plasma, not whole plasma such as Millet et al 21 used, because of the high nonspecific inhibition observed with whole plasma under our experimental conditions. The results of these authors are, however, in agreement with the increased inhibition of Na + fluxes from erythrocytes and the high digoxinlike immunoreactivity of SHR plasma that we described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute plasma vasopressin values obtained by the cytochemical bioassay were comparable to those measured by radioimmunoassay (r ¼ þ0.97, p < 0.001). This assay was later used to study hypertensive rats 41,42 and to determine the vasopressin levels in neonates. 43 One of the major drawbacks to these bioassays was the low throughput of the assay system.…”
Section: The First Bioassay (Acth)mentioning
confidence: 99%
“…W ITH the use of cytochemical techniques 12 we have previously demonstrated that plasma from normal humans 3 and rats 4 on a high sodium intake, from patients with essential hypertension, 3 and from adult spontaneously hypertensive rats (SHR) 6 have a heightened ability to inhibit Na + ,K + -adenosine triphosphatase (ATPase). It therefore appears that these two forms of hereditary hypertension are associated with a rise in the concentration of a cytochemically bioassayable circulating Na + ,K + -ATPase inhibitor that is controlled by salt intake in normal humans and animals.…”
mentioning
confidence: 99%